Benahavís lakes. Plan in which gated communities and Golf courses inside Benahavís municipality turn into water. Data: Benahavís town hall, Google Earth, elaborated by Jorge Minguet. Image base: Google Earth. - Minguet-Medina, Jorge (My University, 2025)
Datos proporcionados en 2019 por el Ayuntamiento de Benahavís y Google Earth, elaborados por el autor y trazados sobre base cartográfica de Google Earth. Data provided in 2019 by Benahavís Town Hall and Google Earth, elaborated by the author and traced over Google Earth cartographic base.
Plan in which gated communities and Golf courses inside Benahavís municipality turn into water. Data: Benahavís town hall, Google Earth, elaborated by Jorge Minguet. Image base: Google Earth. Plan en el que urbanizaciones cerradas y campos de Golf dentro del municipio de Benahavís se convierten en agua. Datos: Ayuntamiento de Benahavís, Google Earth, elaborado por Jorge Minguet. Base de imágenes: Google Earth. Datos proporcionados en 2019 por el Ayuntamiento de Benahavís y Google Earth, elaborados por el autor y trazados sobre base cartográfica de Google Earth. Data provided in 2019 by Benahavís Town Hall and Google Earth, elaborated by the author and traced over Google Earth cartographic base.
Keywords: Benahavís (Málaga) - Mapas; Benahavís; Residential tourism; Gentrification; Touristification; Costa del Sol; Sustainability; Territory; Turistificación; Gentrificación; Turismo residencial; Sostenibilidad; Territorio